Shirley Jackson's Hill House and the rise of meta-gothic parody. Issue 2 (1st October 2020) - Snyder, Travis
This article argues that Shirley Jackson bent her classic gothic tale The Haunting of Hill House into a new genre, the meta-gothic parody. Utilizing a postmodern framing of parody that gestures towards the meta-textual, I reread the humour as presented in the novel as a survival strategy. In utilizing parodic jokes that make fun of classic gothic tropes, some characters are able to survive a haunted house by transcending the genre that they are stuck within. Other characters, unable to change the rules, end up losing the game and getting entrapped. Jackson's book likewise breaks new ground in what is so often lamented as a tired genre.